Políticas de extensão universitária e a disputa pela: a questão dos direitos humanos na UFPB - Zenaide, Maria de Nazaré Tavares (2010)
University Extension Policy and the struggle for hegemony: the question of human rights at UFPB intents to analyze the insertion of the human rights thematic in higher education, from the point of view of their relations with social movements and governmental institutions. To identify practical and educative configurations in human rights, in the period of transition to democracy in Brazil, the study takes as its research field the institutional actions of UFPB on human rights issues in the 1990 s. The thesis is sustained by a critical theory approach: the education on and for human rights it is inserted in the public university in the context of democratic transition, starting with programs of university extension, with a critical perspective of education and across the curriculum, coexisting contradictorily with hegemonic and counter-hegemonic perspectives of human rights, articulating actions of extension to those of teaching, research and institutional management. The objectives of the study were: to rebuild the historical process that made possible the insertion of human rights in actions of university extension in the UFPB; to systematize the actions to create an institutional profile; to investigate the process of institutionalization of human rights in the UFPB, in the general context of Brazilian university, its ramifications in university formation and its articulations with public policies and human rights policies. It takes the form of a case study, with emphasis on qualitative data, through bibliographical, documentary and empirical insertions, involving teachers and technicians who acted in the area of the human rights. The research proved that university extension acted not only as a entrance door for the insertion of the human rights in the university, but it has been also contributing to engage the university in the process of internal democratization, institutionalizing sectors of promotion and defense of human rights and citizenship; and has been socially relevant, preventing violence and forming critically the subjects in order to became protagonists in a emancipatory cultural process. The thesis intends to offer theoretical and practical contributions to the work in favor of human rights in the UFPB and in other universities, social entities and organs.